Moses Maimonides : the man and his works - Davidson, Herbert A. (Herbert Alan), 1932-2021. (New York, N.Y. : Oxford University Press, 2005)
"Moses Maimonides, rabbinist, philosopher, and physician, had a greater impact on Jewish history than any other medieval figure. This book offers a fresh look at every aspect of Maimonides' life and works: the course of his life, his education, his personality, and his rabbinic, philosophical, and medical writings. At a number of junctures, Herbert A. Davidson points out that information about Maimonides which has been accepted for decades or centuries as common knowledge is in actuality supported by no credible evidence and often, more disconcertingly, is patently incorrect. Maimonides' diverse writings are frequently viewed as expressions of several distinct personas, uncomfortably and awkwardly bundled into a single human frame; this book treats his writings as expressions of a single, integrated, albeit complex, mind."--Jacket
Maimonides' life -- Education -- Rabbinic Works I -- Rabbinic Works II -- Rabbinic Works III -- Philosophic Works I -- Philosophic Works II -- Medical works -- Miscellaneous writings
Includes bibliographical references and index
Keywords: Maimonides, Moses, -- 1135-1204; Maimonides, Moses, -- 1135-1204 -- Teachings; Rabbis -- Egypt -- Biography; Jewish scholars -- Egypt -- Biography; Physicians; Clergy; Judaism; Jews; Physicians; Clergy; Judaism; Jews; Egypt; Electronic books; Biography; Biographies